Characterization of Copper Diffusion in Silicon Solar Cells. (April 2015) - Kraft, Achim; Wolf, Christian; Bartsch, Jonas; Glatthaar, Markus
Abstract: In this work we investigate the degradation behavior of solar cells with a copper front side metallization based on a fine-line screen-printed silver seed-layer, a plated nickel diffusion barrier, a plated copper conductive layer and a silver capping. The results reveal that the cell degradation depends, besides the effectiveness of the nickel diffusion barrier, on the used seed-layer and the firing temperature of the seed-layer. The degradation behavior of cells, produced with different Ag seed-layer pastes resulting in different contact finger geometries after screen-printing and firing, was evaluated. With similar nickel diffusion barrier masses the seed-layer that generates the biggest metallized area at the cell surface shows the fastest degradation. Apart from that, the composition of the seed layer also has an impact on the degradation. The analysis of different firing temperatures shows that higher set-peak temperatures result in faster cell degradation due to copper migration.